Examining the impact of gender and household total income on knowledge and government policies on climate change - Suriani Hassan (School of Quantitative Sciences (SQS) UUM College of Arts & Sciences Universiti Utara Malaysia, 2024)
The greatest danger to humanity and nature in the twenty-first century is climate change. The objective of this study is to examine how gender and household total income perceived on five factors of knowledge and government policies support related to climate change. The data stems from a questionnaire survey with 315 respondents. The methodology used in this study are the Mann-Whitney U and Kruskal-Wallis tests. The findings indicate that the distribution of Factor 1 climate change awareness and future perspectives and factor 2 policy integration and coordination differ across categories of gender, whereas the distribution of factor 3 public awareness and low-carbon development, factor 4 understanding climate change impacts and factor 5 strengthening energy policy are the same across categories of gender. The findings also indicate that the distribution of factor 1, factor 2, factor 3 and factor 4 differ across categories of household total income, whereas the distribution of factor 5 is the same across categories of total income of the households. The implication of this study showed while women face unique challenges due to climate change, they also hold significant potential as leaders and contributors to climate solutions despite enhance both their resilience and overall climate response efforts.